Being Parents of First Graders in Primary School: Balancing the Excitement and Anxiety - Zuhal Çeliktürk Sezgin (Anı Publishing, 2020)
The aim of this study is to comprehend the experiences of parents of first graders in primary school. Basic qualitative research approach was adopted in the study. The participants of the survey consisted of 10 parents. In the study the data were collected through semi-structured interview. The interviews were conducted by the researcher in February-March in 2018. Content analysis method was used in analyzing the data. The data collected were classified under themes and sub-themes. The findings indicate that the themese are as follows: being first grader: to start reading and writing again, balance emotions: happiness and anxiety, being parents of first graders: duties and responsibilities, recommendations for first grade parents. According to research findings, it was identified that the most of the students' parents perceived the first year of the primary school as the first year of reading-writing however they feel negative feelings like fear and anxiety along with the positive feelings together with their children. Also parents feel obligated to make their children study and follow-up their lessons. In line with the results of this present study, it is recommended to make an orientation about the first grade primary school (school environment, teacher, other students, lessons) before the education process starts.